Study of Contraceptive Devices Management in The National Health Insurance - Maulana, Afif; Saimi, Saimi; Khalik, Lalu Abdul (poltekkes kemenkes mataram, 2024)
The National Health Insurance or JKN, which was launched on January 1 2014, is intended to increase public access to comprehensive and quality health services, so as to achieve universal health coverage (UHC). Effective promotive-preventive efforts will reduce the incidence of disease and have an impact on reducing the number of sick people and the number of people seeking treatment so that health financing is more efficient. Family planning (KB) services are part of promotive-preventive efforts. In the management of program contraceptive devices provided by the government in the last 3 years, various problems were still encountered, including shortages of contraceptive devices (stock out), accumulation of Alkon in storage warehouses, and Alkon distribution mechanisms that were not smooth. The research was conducted using a descriptive quantitative approach. Research location in East Lombok Regency taking into account the high vacancy of Alkon (Data F/II/KB online). Then, 31 First Level Health Facilities (FKTP) were taken, namely Community Health Centers, Doctor's Practices, Pratama Clinics and Type D Pratama Hospitals. The research was carried out for 6 months, namely May-October 2017. The results of the research show that in general the management of Alkon in the OPD-KB of East Lombok Regency has complied with technical instructions, but there are several mechanisms for providing, storing, distributing, recording and reporting as well as Alkon monitoring and evaluation requires clear and written Standard Operating Procedures (SOP) that refer to technical manuals, and are spread throughout the OPD-KB, UPT-KB, Health Faskes and Network areas, so that the management of the mechanism runs uniformly.